2000
DOI: 10.1121/1.428331
|View full text |Cite
|
Sign up to set email alerts
|

Difference thresholds for intensity perception of whole-body vertical vibration: Effect of frequency and magnitude

Abstract: EnglandRunning title: Whole-body vibration perceptionPublished as: Difference thresholds for intensity perception of whole-body vertical vibration: effect of frequency and magnitude Morioka, M. & Griffin, M. J. 2000 In : Journal of the Acoustical Society of America. 107, 1, p. 620-624.-2 - ABSTRACTDifference thresholds for seated subjects exposed to whole-body vertical sinusoidal vibration have been determined at two vibration magnitudes (0.1 and 0.5 ms -2 r.m.s.) and at two frequencies (5 and 20 Hz). For twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 18 publications
3
48
2
Order By: Relevance
“…In the previous studies of the difference thresholds by Morioka and Griffin 5) and Bellmann et al 6) , it was concluded that there was no frequency dependence of difference thresholds found. It was reported by Morioka and Griffin 5) that there was no statistically significant difference in the difference thresholds between the two vibration frequencies at the two vibration magnitudes used.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In the previous studies of the difference thresholds by Morioka and Griffin 5) and Bellmann et al 6) , it was concluded that there was no frequency dependence of difference thresholds found. It was reported by Morioka and Griffin 5) that there was no statistically significant difference in the difference thresholds between the two vibration frequencies at the two vibration magnitudes used.…”
Section: Discussionmentioning
confidence: 97%
“…It was reported by Morioka and Griffin 5) that there was no statistically significant difference in the difference thresholds between the two vibration frequencies at the two vibration magnitudes used. Although there was a statistically significant difference between the difference thresholds obtained at frequencies of 4 and 16 Hz in this study, the frequencies used in Morioka and Griffin 5) , 5 and 20 Hz, were not used in this study so that discussion based Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reductions of 5% or 10% in vibration magnitude are usually undetectable in subject ratings but, together with other similar changes, they are necessary for the optimisation of comfort [26]. The benefits of changes that are too small to be detected individually can be quantified using current methods of measuring and evaluating vibration.…”
Section: Figure 8 About Herementioning
confidence: 99%